Analisis Monitoring Pelaksanaan Pekerjaan Proyek Pasar Rakyat Bareng Kota Malang - Faris Rizal Andardi; Wisnumurti Wisnumurti; Agus Suharyanto (Department of Civil Engineering, Faculty of Engineering, University of Brawijaya, 2017)
Curve-S, Earned Value, and Tracking. The results of the analysis using the curve method S, week 1 to 6 project acceleration took place, while at week 17, 18, and 19 projects too late. At week 20 the work is accelerated until the last week of the 22nd week, and the duration of the last project is 22 weeks. The result of analysis using Earned Value method, week 17,18,19 late, and other week happened acceleration. Cost deviations occur in weeks 1-4,6,7,15,16,17, and 18. To estimate the final cost of the total final cost, and the prediction for the total project completion time is 22 weeks. The analysis result using tracking shows that the actual duration is 158 days, and the estimated duration is 2 calendar days. The project prediction is completed on January 28, 2017. The total cost incurred is less than the final project cost plan. So the recommendation of the appropriate monitoring method for the People's Market is Tracking.